Focusing and scanning light through a multimode optical fiber using digital phase conjugation - Papadopoulos, Ioannis N.; Farahi, Salma; Moser, Christophe; Psaltis, Demetri (Optics express, 2012)
We demonstrate for the first time to our knowledge a digital phase conjugation technique for generating a sharp focus point at the end of a multimode optical fiber. A sharp focus with a contrast of 1800 is experimentally obtained at the tip of a 105 μm core multimode fiber. Scanning of the focal point is also demonstrated by digital means. Effects from illumination and fiber bending are addressed.